2019
DOI: 10.1186/s10194-019-1042-8
|View full text |Cite
|
Sign up to set email alerts
|

Aura and Head pain: relationship and gaps in the translational models

Abstract: Migraine is a complex brain disorder and initiating events for acute attacks still remain unclear. It seems difficult to explain the development of migraine headache with one mechanism and/or a single anatomical location. Cortical spreading depression (CSD) is recognized as the biological substrate of migraine aura and experimental animal studies have provided mechanisms that possibly link CSD to the activation of trigeminal neurons mediating lateralized head pain. However, some CSD features do not match the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 136 publications
5
39
0
Order By: Relevance
“…During CSD, the cerebral cortex involved in aura symptom generation presents a prolonged depolarization status which overcomes the duration of a usual membrane action potential, thus explaining aura typical duration (5‐60 minutes). Recently, it has been acutely observed that canonical CSD does explain the typical migraine aura manifestations, for example, visual aura followed by contralateral pain, whereas less common migraine aura scenarios, such as pain ipsilateral to aura symptoms, led to the hypothesis that spreading depression can occur in other brain areas 12 …”
Section: Clinical Evidencementioning
confidence: 99%
“…During CSD, the cerebral cortex involved in aura symptom generation presents a prolonged depolarization status which overcomes the duration of a usual membrane action potential, thus explaining aura typical duration (5‐60 minutes). Recently, it has been acutely observed that canonical CSD does explain the typical migraine aura manifestations, for example, visual aura followed by contralateral pain, whereas less common migraine aura scenarios, such as pain ipsilateral to aura symptoms, led to the hypothesis that spreading depression can occur in other brain areas 12 …”
Section: Clinical Evidencementioning
confidence: 99%
“…TBI, including mTBI, might trigger cortical spreading depression (CSD) at the time of injury and be associated with the extent of brain tissue injury and functional outcomes (35). As has been theorized for migraine, CSD might directly activate the trigeminocervical system resulting in headache (36)(37)(38). In fact, some patients with PTH are reported to experience auras with their PTH (12,18,39).…”
Section: Pathophysiologymentioning
confidence: 99%
“…Visual aura symptoms are traditionally attributed to the depolarization phase of CSD and/or CSD-induced hemodynamic changes. However, some features of CSD do not match clinical symptoms of aura; for example, the pre-CSD excitation of cortical neurons, which is thought to underlie positive aura symptoms, seems to be very brief (2–4 sec) to explain the symptoms (6). Our study in awake rats shows that CSD is followed by aberrant cortical activation and hemispheric functional disconnection that last several minutes.…”
Section: Discussionmentioning
confidence: 99%
“…It is thought that a brief burst of neuronal firing before CSD onset produces positive visual symptoms (flashing lights, scintillations) and subsequent depression of neuronal activity underlies negative symptoms (scotoma, blurring of vision). Despite the widely accepted link between CSD and migraine aura, there are several gaps in translating CSD features to clinical aura symptoms and some patterns of aura described in migraine patients cannot be explained based on the known properties of CSD (6). This may be in part due to the fact that most information about CSD and its electrophysiological characteristics has been obtained in anesthetized animals and acute slice preparations.…”
Section: Introductionmentioning
confidence: 99%